1978
DOI: 10.1136/gut.19.11.1049
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive intestinal peptide in man: pharmacokinetics, metabolic and circulatory effects.

Abstract: SUMMARY Graded doses of 0-6, 1'3, and 3.3 pmol/kg/min of vasoactive intestinal peptide (VIP) were intravenously infused over 30 minute periods in four healthy volunteers and plasma VIP levels were measured by radioimmunoassay. Even with the smallest dose of VIP, plasma concentrations rose markedly above normal values. Infusion of higher VIP doses resulted in mean plateau levels of circulating VIP which were in the range of VIP values found in the Verner-Morrison syndrome. After cessation of the VIP infusions, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(60 citation statements)
references
References 20 publications
2
58
0
Order By: Relevance
“…However, like most endogenous peptides, its potential therapeutic applications are limited by its failure to cross the blood-brain barrier (BBB) which strictly controls the access of solutes to the brain (Begley, 1996) and by its rapid elimination after intravenous administration. Its blood half-life is less than 1 min in rat (Hassan et al, 1994) and approximately 1 min in man (Domschke et al, 1978). However, it has recently been shown that a weak amount of VIP appeared to reach the brain in conditions where a large amount of intravenous radiolabelled peptide was administrated (Dogrukol-Ak et al, 2003), which allowed to increase the sensitivity of the brain delivery assays utilized in these studies but also possible risks of side effects of this high concentration of free circulating radiopeptide.…”
Section: Introductionmentioning
confidence: 99%
“…However, like most endogenous peptides, its potential therapeutic applications are limited by its failure to cross the blood-brain barrier (BBB) which strictly controls the access of solutes to the brain (Begley, 1996) and by its rapid elimination after intravenous administration. Its blood half-life is less than 1 min in rat (Hassan et al, 1994) and approximately 1 min in man (Domschke et al, 1978). However, it has recently been shown that a weak amount of VIP appeared to reach the brain in conditions where a large amount of intravenous radiolabelled peptide was administrated (Dogrukol-Ak et al, 2003), which allowed to increase the sensitivity of the brain delivery assays utilized in these studies but also possible risks of side effects of this high concentration of free circulating radiopeptide.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, proteolytic degradation and renal clearance account mainly for the fact that the in vivo half-life of VIP is less than one minute, 14 making its chronic use problematic. Therefore, limiting or preventing proteolytic degradation would be of value in developing VIP as a therapeutic.…”
mentioning
confidence: 99%
“…Studies demonstrate that the entire molecule is required for high-affinity interaction with VIP receptors . Furthermore, in vivo VIP has a half-life of less than 1 min (Domschke et al, 1978). Developing simplified, stable VIP analogs with high affinity for VIP receptors would be useful as prototypes to develop more stable analogs, selective receptor analogs that interact with one of the two G proteincoupled receptors mediating VIP's actions (Harmar et al, 1998), or for in vivo physiological and pathological studies.…”
mentioning
confidence: 99%